Biodiversity valuation and the discount rate problem - Mark Freeman; Ben Groom (2013)
Purpose – The aim of this paper is to demonstrate that the application of standard environmental accounting practices for estimating long-term discount rates is likely to lead to the rejection of biodiversity-sensitive projects that are in the greater societal good. Design/methodology/approach – The authors combine estimates of marginal ecosystem damages from two forestry case studies, one local, one global, with ten different term structures of discount rates taken from both the academic literature and policy choices to calculate present values. Findings – Standard environmental accounting approaches for estimating the long-term discount rate result in the under-valuation of projects that are sensitive to biodiversity conservation. Research limitations/implications – This paper is set within a full cost accounting (FCA) framework, and therefore has the limitations that generally follow from taking this approach to biodiversity problems. Recommended extensions include looking at broader ranges of biodiversity costs and benefits. Social implications – Unless environmental accountants engage with environmental economists over the issue of intergenerational discount rates, then it is likely that socially responsible managers will reject projects that are in the greater societal good. Originality/value – The paper introduces both normative discount rates and declining discount rates to estimates of shadow environmental provisions within FCA and contrasts these with current environmental accounting practices. It also provides two detailed case studies that demonstrate the extent to which biodiversity-sensitive investment choices are likely to be undervalued by managers who follow current accounting recommendations concerning the appropriate choice of discount rate.